Al-Qur’an sebagai Sumber Ilmu Pengetahuan - Silfi Nurmalia Latifah; Cecep Anwar (Gunung Djati Conference Series, 2022)
Al-Qur’an is the holy book that contains all thing that human need, including in the term of science. However, as a science base, al-Qur’an often understood only as a absolutely dogma. The purpose of this research is to present about: 1) the position of al-Qur’an in the human life; 2) the position of science in Islam; and 3) how to learn the Qur’an as a science base capacity. This research is the library research which is including in quantitave research. The result of this research showed that al-Qur’an is the holy book that be a guide for the human to face the problem of life. Al-qur’an also explain the important position of science as a main medium to face the crisis and create a good life. To achieve it, a certain method is needed to understanding the clues and the value of science in the Qur’an. What needs to avoided is using the doctrinal-dogmatis method to understanding the clues of science in the Qur’an, because the field of science is a difference domain with the field of faith.